NIGERIA’S 2015 PRESIDENTIAL ELECTION: BETWEEN DEMOCRATIC CONSOLIDATION AND CHANGE - Durotoye, Adeolu (European Scientific Journal, ESJ, 2015)
The conduct of the 2015 Presidential election in Nigeria recorded mixed outcomes. Although fears that Election Day would be marred by serious violence were allayed to a large extent, some instances of technical hitches, vote buying and other forms of electoral manipulations were recorded in some parts. However, these electoral hitches were not sufficient to alter the expected outcome of the election. For the first time in Nigeria’s political history, an incumbent president lost power in a general election. Has Nigeria’s democracy consolidated satisfactorily? The burden of this paper is to examine the trajectories of the 2015 presidential election relying on both qualitative and quantitative methods of research. The paper concludes that much has to be done if Nigeria’s democracy is to scale the second turn-over test Huntington establishes as the bench mark which if a new democracy survives two turnovers of power, then it has consolidated satisfactorily